Growth and Survival of Vaname Shrimp (Litopenaeus vannamei) Fed with Gracilaria verrucosa - Mifta Jennah; Yudiana Jasmanindar; Wesly Pasaribu (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2024)
This study aims to determine the effect of the addition of Gracilaria verrucosa flour with different doses on the growth and survival of vannamei shrimp. This research was conducted in May-June 2023 at the Dryland Laboratory of the Faculty of Marine and Fisheries Animal Husbandry, Nusa Cendana University, Kupang. This research method uses a completely randomized design with 4 treatments and 3 replicates. Treatment A: as a control (without G. verrucosa flour). Treatment B: addition of 4% G. verrucosa flour. Treatment C: addition of G. verrucosa flour 8%. Treatment D: addition of G. verrucosa flour 12%. The results showed that the addition of G. verrucosa flour in feed was able to increase the growth and survival of vannamei shrimp significantly compared to the control treatment. Treatment D (12% g/kg) addition of G. verrucosa flour gives the best results to increase the growth and survival of vannamei shrimp. The results of the analysis of variance showed that the addition of G. verrucosa flour had a significant effect on the growth and survival of vannamei shrimp